Deposition of Doxorubicin in Rats following Administration of Three Newly Synthesized Doxorubicin Conjugates. (5th December 2013) - Huan, Menglei; Tian, Shuang; Cui, Han; Zhang, Bangle; Su, Dan; Wang, Jieping; Li, Kangchu; Cao, Weidong
Abstract : We previously reported the synthesis of three DOX conjugates that represented different targeting vehicles and showed them to have antitumor activity both in vitro and in vivo . However, the relationships between the pharmacokinetics of these DOX conjugates and their chemical structures were not characterized. In the current study, free DOX derived from each of the conjugates was found at low levels in the rat circulatory system, with conjugated DOX being the major form. The two polyethylene glycol (PEG) conjugates slowly released DOX, and t 1/2 β for total DOX from DOX-LNA, PEG-ami-DOX, and PEG-hyd-DOX was 5.79, 10.22, and 15.18 h, respectively. All three conjugates also deposited less DOX into normal organs than did an equivalent dose of free DOX, and the C max value of free DOX released by DOX- LNA, PEG-ami-DOX, and PEG-hyd-DOX was 32.5, 9.5, and 4.7 μ g/g, respectively. Among the conjugates, the compound with an acid-labile bond between PEG and DOX exhibited the lowest free DOX deposition in healthy tissues, which should decrease the systemic toxicity of free DOX while allowing for tumor targeting by PEG.